Structural insights into the π-π-π stacking mechanism and DNA-binding activity of the YEATS domain - Brianna J. Klein (Nature Portfolio, 2018)
YEATS domains are histone acylation readers that recognize crotonyllysine and acetyllysine. Here the authors provide structural insights into how YEATS domains recognize acetyllysines and further show that the human AF9 YEATS domain also binds DNA.